Cultureel jaarboek, 2002 / : 56e jaargang - Provincie Oost-Vlaanderen (Gent : Provincieraad van Oost-Vlaanderen, 2004)
Beirnaert, Kim ; Benaouisse, Ben ; Bijtebier, Jean-Marie ; Boon, Elke ; De Bruyckere, Berlinde ; Buedts, Raphaël ; Casters, Véronique ; Delvoye, Wim ; Van Dienderen, An ; Gyselbrecht, Martine ; Gyselinck, Erik ; Hoflack, Marc ; Joliet, Ilse ; Marchal, Guy ; Michels, Alex ; Van Neck, Linda ; Van Severen, Dan ; T'Sjoen, Kristof ; Tahon, André ; Vandenberg, Philippe ; Verhelst, Christian ; Volckaert, Didier
boek